(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study assessed mentoring practices influencing business educators in Edo and Delta States. Two research questions guided the study while three null hypotheses were tested at 0.05 level of significance. The study adopted a descriptive survey design using asample of 231 business educators. A 16-item questionnaire was utilized for the study. The Cronbach’s alpha was used to determine the reliability of the instrument, which yielded co-efficient of .95 and 0.85 for the two sub-sections of the instrument with an aggregate reliability of 0.90. Mean and standard deviation were used to answer the research questions. The z-test and analysis of variance (ANOVA) were used to test the null hypotheses. The findings of the research questions revealed that formal mentoring does not influence business educators. Informal mentoring was found to be the dominant mentoring practice influencing business educators in Edo and Delta States. Hypotheses testing showed no significant difference on mentoring practice of business educators either by gender, types of tertiary institutions or state of domiciliation of institution. This implies that management of tertiary institutions in Edo and Delta States neither plans, implements nor evaluates mentoring practices for business educators. It was therefore concluded that mentoring practices for business educators in Edo and Delta States is inadequate to meet business educators’ career growth and development needs. It was therefore, recommended among others that authorities of tertiary institutions in Edo and Delta State especially of Department of Business Education should compulsorily institute formal mentoring practice in addition to the available informal professional mentoring for business educators. This could help to give more opportunities to the young/inexperienced business educators to learn from the wealth of experience of the older and more experienced business educators so as to enhance their professional commitment.